Who Reports the Mood in German Boardrooms? Evidence from the ifo Business Survey - Jonas Hennrich; Stefan Sauer; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2023)
The ifo Business Climate Index for Germany is considered as the most important leading indicator for the German economy. Media reports often refer to the mood in German boardrooms. Based on a survey conducted in May 2023, we show that most of the around 9,000 respondents to the monthly ifo Business Survey are the owners or managers of the companies. The sentiment regarding the state of the German economy thus comes directly from the boardrooms of the companies..
Keywords: C80; C81; C83; 330; ifo business Survey; firms; answering behaviour